Peculiar morphologies of extended extragalactic radio sources from numerical simulations - Lacatus, D.A.; Badea, M.; Paraschiv, A.R.; Tesileanu, O. (Advances in Astronomy and Space Physics, 2011)
Among the extragalactic radio sources there are objects with unusual morphologies. We investigated the possibility that the propagation of jets in a stratified distribution of density may produce such effects. A numerical setup was worked out and hydrodynamical 2D simulations were performed using the PLUTO code. We carried out a parametric study of a jet launched along the main axis of the mass distribution in order to obtain important sideways features.